Utilization Of Zakat, Infaq, And Alms (Zis) That Is Productive Of Transparency And Accountability In Indonesia - Ingsun Kumala Irti; Heri Susanto (Proceeding International Seminar of Islamic Studies, 2019)
Amil zakat agency is an institution that manages zakat formed by the government, consisting of elements of government and society with the task of collecting, distributing and empowering the use of zakat. As this is done by the National Amil Zakat Agency (BAZNAS). As a zakat management institution, BAZNAS must be able to provide concrete evidence to the community in utilizing productive zakat which is right on target and successfully combats poverty. Therefore good zakat governance (good zakat governance) is transparency and accountability in the management of zakat which includes the management of infaq / alms. As fund management for people who rely on donors from the people, transparency and accountability in the management of Zakat and Infaq / Alms (ZIS) are the main concerns of the Zakat Processing Organization (OPZ). The more transparent and accountable OPZ is in managing ZIS, the higher the public's trust in OPZ. High trust in OPZ will foster awareness, compliance and motivate the community (Muzakki) to voluntarily distribute zakat, donations through the official OPZ (BAZNAS). A proper financial accounting and reporting system can realize transparency and accountability of an OPZ. To produce a proper financial accounting and reporting system, creating uniformity and comparability in financial reporting and so that OPZ is ready to be audited by public accountants, the bookkeeping activities and preparation of OPZ financial statements refer to a standard guideline that is zakat and infaq / alms accounting standards. ZIS accounting standards applicable in Indonesia are Statement of Financial Accounting Standards (PSAK) number 109 concerning zakat and donation / alms accounting issued by the Indonesian Institute of Accountants (IAI) PSAK no. 109 is used as a guideline for OPZ in the recognition, measurement, presentation and disclosure of zakat and infaq / alms transactions.